The relationships among the logic of value innovation, strategic decisions and market-driven factors - Senturk, HayatAyar; Ozkan, Kaan Tugrul (EMERALD GROUP PUBLISHING LTD, 2023)
PurposeThe logic of value innovation has received increased attention in the strategic marketing and innovation literature. Studies investigating how value innovation, as a firm's strategic mindset, contributes to creating new market space through more proximal market-driven factors such as strategic decisions and customer value are still lacking, nevertheless. This study aim to investigate how the logic of value innovation influences creating new market space through quantum strategy and customer value creation. Design/methodology/approachSurvey data from a sample of 204 manufacturing and service firms was used to test the conceptual model and research hypotheses. The data were analyzed using structural equation modeling. FindingsThe findings reveal the direct and indirect effect of value innovation logic on the new market space through the mediation of quantum strategy and customer value creation. Besides, this study shows that quantum strategy does not directly contribute to customer value creation. A reason is that the quantum strategy as a both/and strategy is the more dominating factor in creating new market space. Originality/valueThere is still a lack of a systematic understanding of how value innovation, as a firm's strategic mindset, contribute to creating new market space through a firm's strategic choices and superior customer value creation, as more proximal market-driven factors. This study empirically attempted to address this research problem. This study contributes to the strategic marketing literature by providing a model for the interwoven relationships between value innovation, quantum strategy, customer value and new market space.
Keywords: The logic of value innovation; Quantum strategy; Customer value; New market space; CUSTOMER VALUE CREATION; COMPETITIVE ADVANTAGE; PERFORMANCE; INDUSTRY; CAPABILITIES; WORK; Business & Economics